Public policies and climate change: contributions to the problem of the multilevel coordination based on an analysis of municipal policies - Dalla Torre, Matías; Coronel, Diego (Estado, Gobierno y Gestión Pública, 2020)
Climate change is an imperative of this time and its consequences on social life, are the main challenge for governments and their public policies. What contributions are generated by municipal policies on climate change and on the commitments assumed by countries in international agreements? What are the main impacts of multilevel government coordination problems in the implementation of municipal policies against climate change? Based on these questions, and from a strategy that combines quantitative and qualitative methodologies, the article investigates the main coordination problems in the implementation of climate change policies, based on the study of the policies implemented by a municipality in the Province from Mendoza, Argentina.